Optimizing Market Entry in Emerging Economies: DEA and Neutrosophic-Z MCDM Approach for Chinese Oil and Gas Equipment Manufacturers - Nguyen, Phi-Hung; Nguyen, Lan-Anh Thi; Pham, The-Vu; Vu, Tra-Giang; Nguyen, Van-Khanh; Vu, Duc-Minh; Nguyen, Thu-Hoai Thi (Optimality, 2025)
This study addresses the challenge of optimizing international market entry decisions for Chinese petroleum equipment manufacturers in emerging economies. As global competition intensifies, effective market selection and entry strategy prioritization become crucial for successful expansion. This study employs an innovative integrated approach combining Data Envelopment Analysis (DEA), Malmquist and Neutrosophic Z-number Multi-Criteria Decision Making (MCDM) methods to evaluate market efficiency and prioritize entry strategies. The DEA Malmquist analysis assessed the efficiency and productivity changes of 35 countries from 2013 to 2019, categorizing them into highly efficient, stable, and inefficient markets. Subsequently, the Neutrosophic Z-number MCDM method prioritized specific entry strategies for each market category. Results reveal distinct strategy priorities: highly efficient markets emphasize technological capability and strategic sourcing; stable markets focus on regional consolidation and standardized training; inefficient markets prioritize regulatory compliance and product customization. This integrated approach provides a comprehensive framework for market analysis and strategy formulation, offering valuable insights for Chinese manufacturers in their global expansion efforts. The study contributes to international business strategy literature by demonstrating the effectiveness of combining quantitative efficiency analysis with expert judgment under uncertainty, while also providing practical implications for decision-makers in the petroleum equipment industry.